Causes of the Occurrence of Crime Gambling - Muslih; Bastianto Nugroho; Supolo Setyo Wibowo1 (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
The aim of the research is to avoid criminal acts of gambling and to make people aware of how dangerous gambling is and the impact it has on the family. The method used is the problem approach that the authors use is a normative juridical approach. Which means the problems in the field are juxtaposed with the existing legal aspects. Law is conceptualized as what is written in laws and regulations (law in books) or law is conceptualized as rules or norms which are standards for human behavior that are considered appropriate. result b. If viewed from a juridical aspect, the matter of gambling is regulated in the Criminal Code, namely Article 303 and Article 303 bis and strengthened by Law no. 7 of 1974 concerning Controlling Gambling. Until now, the exact rules regarding the prohibition of gambling are still unclear. Judging from this provision, there is actually no prohibition for the public to gamble. In this article, what is prohibited is the holding of gambling without obtaining a permit. While Law no. 7 of 1974 is not a Law on the Prohibition of Gambling, because its contents are regulations for the implementation of gambling (bookies), so that they seek permission to organize gambling. In another sense, gambling is permitted under the law if it has complete permits. Because it is very possible that the maximum fine is imposed cumulatively. Because the burden of proof is placed on law enforcers. In Indonesia, it is indeed not easy to investigate assets resulting from a crime or those that have been laundered. In fact, in various kinds of news lately, many law enforcement officials have played a role, were involved or